OP XI – 5 The proportion of high noise sensitivity and annoyance in the hermes cohort study of swiss adolescents. (18th March 2018) - Tangermann, Louise; Saucy, Apolline; Vienneau, Danielle; Schäffer, Beat; Wunderli, Jean Marc; Röösli, Martin
Abstract : Background/aim: The World Health Organization considers children to be of particular risk of suffering negative cognitive and health consequences through exposure to transportation noise. However, little is known about how adolescents experience exposure to noise in their everyday life. The purpose of this study is to examine level of both noise annoyance and sensitivity in a cohort of adolescents. Methods: Noise sensitivity and annoyance was measured in a cohort of 892 participants aged 12 to 17 with one year follow-up. Noise annoyance for five different noise sources, including transportation vehicles, industry and people, was measured using a verbal 4 point Likert scale, where the annoyance was classified as follows: none (0), little (1), clearly (2), severely (3). Participants were classified as highly annoyed if they scored 2 or higher. Noise sensitivity was measured with the Zimmer/Ellermeyer (1998) scale ranging from 0 to 27. Individuals were classified as sensitive if they had a score over 13.5. Proportion of noise annoyed and noise sensitive participants are presented. Change between baseline and follow-up proportions were compared with the McNewmar-test. Results: 847 students participated at the baseline measurement of the annoyance of road noise. Follow-up participation was at 806 (participation rate: 95.1%). The proportion of highly annoyed students was 4.40% (n=39) at baseline and 2.74% (n=23) at follow-up. The change in proportion after a year was quite significant (p=0.028). The noise sensitivity questionnaire was filled out by 887 students at baseline and follow-up was at 840 (participation rate: 94.7%). The proportion of highly noise sensitive students was 24.32% (n=206) at baseline and 24.07% (n=194) at follow-up, with no indications for a difference between baseline and follow-up (p=0.834). Within all comparisons gender was not substantial, except for baseline noise annoyance of two noise sources. Conclusion: Our study suggests that prevalence of high noise annoyance is low in this age group and tends to decrease during puberty. Noise sensitivity seemed to be prevalent in a quarter of adolescents and stayed constant after a year. Future analyses should explore the relationship between annoyance, sensitivity, actual noise exposure and health outcomes.